1995
DOI: 10.1016/0735-1097(95)80015-9
|View full text |Cite
|
Sign up to set email alerts
|

Coronary angioplasty of chronic total occlusions with bridging collateral vessels: immediate and follow-up outcome from a large single-center experience

Abstract: Coronary angioplasty can open chronic total occlusions, with or without bridging collateral channels, for safe and effective recanalization without major complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
95
1
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(107 citation statements)
references
References 19 publications
10
95
1
1
Order By: Relevance
“…To facilitate guidewire crossing, new guidewires have been developed, including a ball-tipped wire [2], the laserwire [3], guidewires with hydrophilic coating [4], and stiff wires with high-torque control (Athlete wire, Asahi Intech, Japan). Except for one study [5], these have failed to improve the success rate significantly. The lack of visualization to navigate safely the guidewire through the occlusion site is a major cause of failure.…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate guidewire crossing, new guidewires have been developed, including a ball-tipped wire [2], the laserwire [3], guidewires with hydrophilic coating [4], and stiff wires with high-torque control (Athlete wire, Asahi Intech, Japan). Except for one study [5], these have failed to improve the success rate significantly. The lack of visualization to navigate safely the guidewire through the occlusion site is a major cause of failure.…”
Section: Introductionmentioning
confidence: 99%
“…This might be considered a failure of conventional 2D-angiography to properly represent stump morphology and true lesion geometry (Safian et al, 1988;Kinoshita et al, 1995). Moreover CTOs are often long lesions length, with severe calcifications and tortuosity (Di Mario et al, 2007), therefore the evaluation of these complex geometric factors is difficult with conventional 2D angiography, often leading to misjudgement of the potential and proper method of treatment (Herrington et al, 1993b).…”
Section: Qca In Chronic Total Occlusionmentioning
confidence: 99%
“…Complication rates of CTO PCI were traditionally too high to justify these procedures and success rates were based predominantly on individual operator skills and annual case volume [60,61]. A review of the NHLBI Dynamic Registry revealed a decrease of CTO PCI atempts from 9.6% in 1997/1998 to 5.7% in 2004 [62].…”
Section: Percutaneous Intervention Of Ctomentioning
confidence: 99%
“…Over time, with the improvement of both equipment such as microcatheters and dedicated guidewires with greater torque response [98] and recanalization techniques such as retrograde procedures, safe and efective CTO PCI became possible [60] and most of the prior obstacles vanished [99].…”
Section: Procedural Success In Patients With Cto Undergoing Pci or Cabgmentioning
confidence: 99%
See 1 more Smart Citation